Folate-based single cell screening using surface enhanced Raman microimaging. Issue 39 (26th September 2016) - Fasolato, C.; Giantulli, S.; Silvestri, I.; Mazzarda, F.; Toumia, Y.; Ripanti, F.; Mura, F.; Luongo, F.; Costantini, F.; Bordi, F.; Postorino, P.; Domenici, F.
Abstract : A SERS active nanovector based on folic acid allowed for selectively targeting cancer cells, achieving SERS diagnostics at single cell level. Abstract : Recent progress in nanotechnology and its application to biomedical settings have generated great advantages in dealing with early cancer diagnosis. The identification of the specific properties of cancer cells, such as the expression of particular plasma membrane molecular receptors, has become crucial in revealing the presence and in assessing the stage of development of the disease. Here we report a single cell screening approach based on Surface Enhanced Raman Scattering (SERS) microimaging. We fabricated a SERS-labelled nanovector based on the biofunctionalization of gold nanoparticles with folic acid. After treating the cells with the nanovector, we were able to distinguish three different cell populations from different cell lines (cancer HeLa and PC-3, and normal HaCaT lines), suitably chosen for their different expressions of folate binding proteins. The nanovector, indeed, binds much more efficiently on cancer cell lines than on normal ones, resulting in a higher SERS signal measured on cancer cells. These results pave the way for applications in single cell diagnostics and, potentially, in theranostics.